(untitled) (Confluenţe Bibliologice, 2026)
At the book launch of composer Gheorghe Mustea participants were invited to listen his music. All genres of music created by the composer have been presented: symphonic music, vocal-symphonic, opera, chamber (vocal and instrumental), choral, theatre and ﬁlm, light-music and popular style. The book containes an audio CD.